Spatial distributions of iron and manganese in surface waters of the Arctic's Laptev and East Siberian seas - N. Kanna; K. Tateyama; T. Waseda; A. Timofeeva; M. Papadimitraki; M. Papadimitraki; L. Whitmore; H. Obata; D. Nomura; D. Nomura; D. Nomura; H. Ogawa; et al. (Biogeosciences)
The Arctic Laptev and East Siberian seas (LESS) have high biogeochemical activity. Nutrient inputs associated with river runoff and shelf sediment–water exchange processes are vital for supporting primary production in the LESS. Relative to macronutrients, data on dissolved iron (dFe) and manganese (dMn), which are essential micronutrients for primary producers, have historically been sparse for LESS. Some dFe and dMn are reportedly carried in the central Arctic by the Transpolar Drift, a major current that directly transports Eurasian shelf water, river water, and sea ice from the LESS continental margins. However, the supply of dFe and dMn to the surface waters of the LESS and the subsequent biogeochemical processes are not well constrained. In the summer of 2021, we investigated the following questions: what are the sources of dFe and dMn in the surface layer and which factors control their concentrations and distributions on the LESS continental margins? We demonstrated strong regional controls on dFe and dMn distributions based on distinct hydrographic regimes between the eastern side of the LESS (East Siberian Sea and Chukchi Abyssal Plain) and the western side (Makarov and Amundsen basins). Specifically, the East Siberian Sea and Chukchi Abyssal Plain were governed by Pacific-sourced water, and the Makarov and Amundsen basins were influenced by Atlantic-sourced water. Pacific-sourced water contained higher levels of dMn released from continental shelf sediments than Atlantic-sourced water. In contrast, elevated dFe signals were not observed, likely because sedimentary dFe was more rapidly removed from the water column through oxidation or scavenging than dMn was. The impact of river water discharge on the dFe distributions of Pacific- and Atlantic-sourced water was significant. A positive correlation between the fraction of meteoric water (river water and precipitation), dFe, and humic-like colored dissolved organic matter (CDOM) in these waters confirmed that dFe and CDOM are common freshwater sources. Terrigenous organic ligands likely stabilize Fe in the dissolved phase, which is not the case for Mn. Sea ice melting and formation were not significant sources during the observation period. We conclude that the major sources controlling the dFe and dMn distributions on the LESS continental margins are river discharge and shelf sediment input.